Penyisihan Piutang Tak Tertagih Sebagai Alat Manajemen Laba - Midiastuty, Pratana Puspa; Fitri, Via Rafiqa; Suranta, Eddy; Hanafi, Fachruzzaman (Jurnal Profita: Komunikasi Ilmiah Akuntansi dan Perpajakan, 2023)
The purpose of this study is to prove the effect of earnings thresholds such as loss avoidance and previous years’ earnings, and moderation between previous years’ earnings and tax expenses can decrease bad debt expense. The theory used in this study is the agency theory.The population of this study is firms in non-financial sector listed in Indonesian Stock Exchange from 2014-2017. The method of sample collection used purposive sampling technique. The sample consisted of 79 firms and 316 observations. Data analysis was performed with multiple regression analysis using SPSS. The data used in this study is secondary data obtained from the financial data at website web.idx.id. The results of the study showed that loss avoidance proved can decrease bad debt expense. Previous years’ earnings proved can’t decrease bad debt expense, and tax expenses proved not to moderate the influence of previous years’ earnings and bad debt expense